Designing the UI/UX of the 'Skintopia' Skincare Application Using a User-Centered Design Approach - Marylda Salma Wajendra Dewi; Seftin Fitri Ana Wati; Iqbal Ramadhani Mukhlis (Universitas Islam Kuantan Singingi, 2025)
In recent years, public interest in skincare has significantly increased, especially among younger generations. Although various skincare applications offering skin analysis features are already available, most of them still have limitations. These include product recommendations that are focused only on specific brands, the lack of validation by dermatologists, and the absence of a fully integrated skincare solution within a single platform. This study aims to develop a mobile skincare application called Skintopia, with a focus on user needs through the application of the User-Centered Design (UCD) method. The System Usability Scale (SUS) evaluation results showed scores of 92 from skincare users and 89 from dermatologists. Both scores fall under the “Excellent” category, receiving a grade of A and classified within the “acceptable” level of acceptability. These findings indicate that the UI/UX design of the Skintopia application successfully meets user needs and provides an intuitive and user-friendly experience.